PENINGKATAN KUALITAS PEMBELJARAN EXPLANATION TEXT MENGGUNAKAN MODEL PROBLEM BASED LEARNING - prakoso, rival (Jurnal Ilmiah Pendidikan Profesi Guru, 2021)
AbstractEnglish is one of important language courses in high school level. There are many skills to be mastered in English. One of many ways to improve the quality of English teaching and learning is by implementing problem based learning model. The lesson study is administered in three cycles which are; plan, do, and see. The focus of the study is to discover the strengths and weaknesses in a teaching learning process. in addition, the data during the teaching and learning process in the class is recorded and discussed with the team. Furthermore, the result will be reflected to the next class meeting. The result of lesson study showed that problem based learning model was effective enough to be implemented in English learning. Furthermore, the overall implementation of lesson study was safe and sound even though there are some minor hurdles during the teaching learning process.Â Keywords : Writing, Lesson study, Problem based learning.